Estimation of Atmospheric IR Absorption - Adams , Barry D. O. (Current Advances in Geography, Environment and Earth Sciences Vol. 3, 2022)
In this work, we present a program to numerical integrate the atmospheric absorption due to carbon dioxide and water vapour of infrared photons by the atmosphere. We also investigate the effect of water evaporation on climate sensitivity. We present a prediction of increase temperature from doubling CO_2 of just under a fifth of a degree.